The Combination of Three Components Derived from Sheng MaiSan Protects Myocardial Ischemic Diseases and Inhibits Oxidative Stress via Modulating MAPKs and JAK2-STAT3 Signaling Pathways Based on Bioinformatics Approach - Li, Fang; Zhang, Yu; Zeng, Donglin; Xia, Yu; Fan, Xiaoxue; Tan, Yisha; Kou, Junping; Yu, Boyang (Frontiers in Pharmacology, 2017)
GRS is a drug combination of three components including ginsenoside Rb1, ruscogenin and schisandrin. It derived from the well-known TCM formula Sheng MaiSan, a widely used traditional Chinese medicine for the treatment of cardiovascular diseases in clinic. The present study illuminates its underlying mechanisms against myocardial ischemic diseases based on the combined methods of bioinformatic prediction and experimental verification. A protein database was established through constructing the drug-protein network, and a target-pathway interaction network was constructed to identify potential pathways and targets of GRS in the treatment of myocardial ischemic diseases. Several target proteins, such as NFKB1, STAT3 and MAPK14, were identified as the candidate key proteins, and MAPKs and JAK-STAT signaling pathway were suggested as the most related pathways, which were in accordance with the gene ontology analysis. Then, the predictive results were further validated and we found that GRS treatment alleviated hypoxia/reoxygenation (H/R)-induced cardiomyocytes injury via suppression of MDA levels and ROS generation, and potential mechanisms might related to the suppression of activation of MAPKs and JAK2-STAT3 signaling pathways. In conclusion, our findings provide the evidence that GRS ameliorates myocardial ischemia injury linked with modulating oxidative stress and MAPKs and JAK2-STAT3 signaling pathways, which provided some new insights for its prevention and treatment of myocardial ischemia diseases.